A meta-analysis of techniques to promote motivation for health behaviour change from a self-determination theory perspective. Issue 1 (2nd January 2019) - Gillison, Fiona B.; Rouse, Peter; Standage, Martyn; Sebire, Simon J.; Ryan, Richard M.
ABSTRACT: A systematic review and meta-analysis was conducted of the techniques used to promote psychological need satisfaction and motivation within health interventions based on self-determination theory (SDT; Ryan & Deci, 2017. Self-determination theory: Basic psychological needs in motivation, development, and wellness . New York, NY: Guilford Press). Eight databases were searched from 1970 to 2017. Studies including a control group and reporting pre- and post-intervention ratings of SDT-related psychosocial mediators (namely perceived autonomy support, need satisfaction and motivation) with children or adults were included. Risk of bias was assessed using items from the Cochrane risk of bias tool. 2496 articles were identified of which 74 met inclusion criteria; 80% were RCTs or cluster RCTs. Techniques to promote need supportive environments were coded according to two established taxonomies (BCTv1 and MIT), and 21 SDT-specific techniques, and grouped into 18 SDT based strategies. Weighted mean effect sizes were computed using a random effects model; perceived autonomy support g  = 0.84, autonomy g  = 0.81, competence g  = 0.63, relatedness g  = 0.28, and motivation g  = 0.41. One-to-one interventions resulted in greater competence satisfaction than group-based ( g  = 0.96 vs. 0.28), and competence satisfaction was greater for adults ( g  = 0.95) than children ( g  = 0.11). Meta-regression analysis showed that individual strategies had limited independent impact on outcomes, endorsing the suggestion that a need supportive environment requires the combination of multiple co-acting techniques.